Shifting the paradigm to letrozole as first-line ovulation induction in pcos: a review of efficacy and safety - Juwana Janu; Reny Haryani (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Polycystic ovary syndrome (PCOS) is a primary cause of anovulatory infertility. While clomiphene citrate (CC) has been the traditional treatment, letrozole (LE) has emerged as a superior alternative with better clinical outcomes. Purpose: to evaluate the clinical efficacy, safety, and biological mechanisms of LE compared with CC in ovulation induction for PCOS patients. Method: A comprehensive literature search was conducted on PubMed and Google Scholar for studies published between 2021 and 2026. Seven high-quality articles, including randomized controlled trials (RCTs) and meta-analyses, were selected for synthesis. Results: The synthesis of the literature indicates that LE significantly increases the live birth rate by 54% (RR 1.54) and improves ongoing pregnancy rates compared with CC. LE is more efficient, showing a shorter time to ovulation (17.2 vs 24.1 days) and higher success in obese patients (BMI > 30). Mechanistically, LE superiorly enhances endometrial receptivity by significantly increasing Integrin αvβ3 and VEGF expression, as well as the Endometrial Flow Index (FI). Furthermore, LE demonstrates a superior safety profile with a 58% lower risk of multiple pregnancies and minimal incidence of ovarian hyperstimulation syndrome (OHSS). Conclusion: Letrozole is more effective and safer than CC, primarily due to its beneficial impact on the endometrial microenvironment. LE could be implemented as the universal first-line treatment for infertility in women with PCOS. Suggestion: For clinicians, LE can be considered as the universal first-line therapy for ovulation induction in patients with PCOS, replacing CC. From a health service policy perspective, standard protocols in fertility clinics need to be updated to integrate LE use in order to improve pregnancy success and reduce long-term costs due to complications of multiple pregnancy